Proposing a Solution for Vocation and Interdisciplinary Training Model - Trần Thu Hà; Nguyễn Minh Khoa (Journal of Technical Education Science, 2006)
Interdisciplinary and Articulation training are one of direction for development in Vietnam nowadays, in order to made a chance for learner and to develop human resource with high occupational skill to satisfy for socioeconomic needs. Aim at objective to have a good satisfying to give necessary requirements for development the economy in Ho Chi Minh city and Vietnam today, as Human source with high occupational skill, to bring articulation of curriculums are essential. Thịs programs to made a chance for learner have adapted oneself to modern technology. To couple vocation and interdisciplinary training will get “professional skill of engineer”interdisciplinary to satisfy for company needing. All of them are contribute a fair competition for society. In there, to couple vocation and interdisciplinary training today, are fresh heading in Vietnam, at present some universities to perform this model which has the advantage, but they are show shortcomings in practice. Authors want to share some of experience and to put for forward solution to perfect this training model in order to introduce and to receive feedback for contruction “To couple vocation and interdisciplinary training”model to satisfy for development of industry.